BETWEEN AGRICULTURE AND COAL MINING: A STUDY OF THE LAND GRABBING IN THE SUB-DISTRICT OF TENGGARONG SEBERANG - Robert Siburian (LIPI Press, 2015)
Tenggarong Seberang subdistrict had been an agriculture area since the 1980s which was started when migrants were located there. The subdistrict had ever been a rice granary for Kutai Kartanegara Regency. To support the agricultural activity, the regency goverment developed a rice processing unit to increase the quality of rice from that place. However, while the coal mining activity around Tenggarong Seberang is increasing, at the same time the agricultural land has changed its function become a mining concession. Land grabbing has emerged between peasants who are consistant to work in agriculture and those who see the mining as an economic sector which will bring a more advance life. This paper attempts to understand how the peasants survive in their agricultural activity with all obstacles and from mining industry which continuously push to the agricultural areas. This paper is based on the research conducted in 2014. Keywords: agriculture, mining, competition, and political ecology